2011
DOI: 10.1007/s12088-011-0080-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Arsenic on Nodulation and Nitrogen Fixation of Blackgram (Vigna mungo)

Abstract: Rhizobium-legume symbiotic interaction is an efficient model system for soil remediation and reclamation. We earlier isolated an arsenic (As) (2.8 mM arsenate) tolerant and symbiotically effective Rhizobium strain, VMA301 from Vigna mungo and in this study we further characterized its efficacy for arsenic removal from the soil and its nitrogen fixation capacity. Although nodule formation is delayed in plants with As-treated composite when the inoculum was prepared without arsenic in culture medium, whereas it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 22 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Additionally, metal­(loid)­s, including Fe and As, also correlated with diazotroph abundance, as revealed by RF. Consequently, high metal contamination and toxicity may impede diazotrophic activities. …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, metal­(loid)­s, including Fe and As, also correlated with diazotroph abundance, as revealed by RF. Consequently, high metal contamination and toxicity may impede diazotrophic activities. …”
Section: Discussionmentioning
confidence: 99%
“…The effects of metals on rhizobial composition within soil or nodule environment and different legume genotypes, however, have been contradictory (Wani et al 2007a(Wani et al , b, 2008a. Mandal et al (2011) reported that nitrogenase activity was reduced to almost 2 fold in plants with Arsenate-treated soil but not abolished in root nodule of blackgram. Their microscopic observations of the cross section of root nodules revealed that the effective areas of N 2 -fixing zone were reduced in plants grown in arsenic contaminated field.…”
Section: Rhizobium-legume Molecular Signalling Exchange Noduation Anmentioning
confidence: 99%
“…Usually, the changes detected are as expected for such concentration (Abbas et al, 2018). Although originally the inoculation of diazotroph microorganisms had a sole and important function, to serve as a nitrogen source for crops in order to improve growth and increase yield, the utilization of such microorganisms as bioremediation tools constitutes an additional function that has gained special attention in the last 10 years (Gómez‐Sagasti & Marino, 2015; Mandal et al, 2011; Reichman, 2007). In addition, physico‐chemical transformations of metal(oid)s carried out by microorganisms in the rhizosphere depend on their intrinsic capacities (Finnegan & Chen, 2012; Lomax et al, 2012; Yang & Rosen, 2016).…”
Section: Discussionmentioning
confidence: 99%